Positive margins in excised dermatofibrosarcoma protuberans: a study of 58 cases treated with slow‐Mohs surgery. (12th August 2013) - Serra‐Guillén, C.; Llombart, B.; Nagore, E.; Requena, C.; Traves, V.; Llorca, D.; Kindem, S.; Alcalá, R.; Guillén, C.; Sanmartín, O.
Abstract Background Dermatofibrosarcoma protuberans (DFSP) is characterized by unpredictable subclinical extension, meaning that positive margins are frequently detected following conventional surgical excision. Objective To study the presence or absence of residual tumour in DFSP with positive margins after conventional surgery and identify possible predictors of residual tumour or clear margins following a single Mohs micrographic surgery (MMS) stage. Methods A retrospective study of patients with DFSP and positive margins following conventional excision referred for MMS was performed. We studied gender, age, tumour site, time from presentation to diagnosis, and affected margins. Results We studied 58 cases, 35 (60.3%) of which had histological evidence of residual tumour. Tumours of the head and neck were significantly associated with the persistence of tumour. A single MMS stage was sufficient to achieve clearance in the majority of cases (n = 46). All tumours with lateral involvement only were resolved with a single Mohs stage. Conclusions DFSPs with positive margins after conventional surgical excision should undergo re‐excision because the majority have histologic evidence of residual tumour. Re‐excision with 1‐cm margins beyond the scar could be an option in certain tumour sites, particularly when it is known which margins are involved.